2020
DOI: 10.1038/s41598-020-72463-z
|View full text |Cite
|
Sign up to set email alerts
|

On-chip protein separation with single-molecule resolution

Abstract: Accurate identification of both abundant and rare proteins hinges on the development of single-protein sensing methods. Given the immense variation in protein expression levels in a cell, separation of proteins by weight would improve protein classification strategies. Upstream separation facilitates sample binning into smaller groups while also preventing sensor overflow, as may be caused by highly abundant proteins in cell lysates or clinical samples. Here, we scale a bulk analysis method for protein separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…Classic approaches such as reductive amination with aldehydes or acylation with NHS esters, which rely on pH control residues in short polypeptides through specific coupling to fluorescent tags while using a solid-state nanopore with low fluorescence background 80 . In all these approaches, separating the proteins by mass before single-molecule sensing may have greatly facilitated the identification of proteins in complex samples containing many different proteins 81 . Nanopore protein fingerprinting can make extensive use of advanced deep learning artificial intelligence (AI) strategies to identify patterns in noisy signals.…”
Section: Box 4 | Chemistry Concepts In Protein Sequencingmentioning
confidence: 99%
“…Classic approaches such as reductive amination with aldehydes or acylation with NHS esters, which rely on pH control residues in short polypeptides through specific coupling to fluorescent tags while using a solid-state nanopore with low fluorescence background 80 . In all these approaches, separating the proteins by mass before single-molecule sensing may have greatly facilitated the identification of proteins in complex samples containing many different proteins 81 . Nanopore protein fingerprinting can make extensive use of advanced deep learning artificial intelligence (AI) strategies to identify patterns in noisy signals.…”
Section: Box 4 | Chemistry Concepts In Protein Sequencingmentioning
confidence: 99%
“…c) Top: a magnified white light view of the main channel showing the polymer plug section in which proteins are separated by mass/charge. Bottom: Fluorescence images of: c‐i) the labeled proteins during loading into the double “T” junction, c‐ii) stacking at the liquid/polymer interface, and c‐iii) during electrophoretic migration in the polymer plug (reproduced with permission [ 26 ] Copyright 2020, NPG). d) Fluorescence Kymograph of a run consisting of four labeled proteins with different molecular weights, visibly separated along the channel.…”
Section: Ultra‐high Aspect Ratio Solid‐state Fluidic Device For Singl...mentioning
confidence: 99%
“…We found that the solid material fabrication was necessary to support the high aspect ratio of the device, without collapsing. [ 26 ] The filling zone of the devices consisted of a double “T” offset junction, which defined a precise sample volume loading of 4 pL. This is an outstanding feature of our device because ultra‐small volume analysis represents an ongoing challenge for current methodologies.…”
Section: Ultra‐high Aspect Ratio Solid‐state Fluidic Device For Singl...mentioning
confidence: 99%
“…We found that the solid material fabrication is necessary to support the high width/height aspect ratio of the device, without collapsing. 25 The filling zone of the devices consists of a double "T" offset junction, which defines a precise sample volume loading of 4 pL. This is an outstanding feature of our device since ultra-small volume analysis represents a significant challenge for the currently established detection methodologies.…”
Section: Ultra-thin Solid State Nano-fluidic Device For Single Protei...mentioning
confidence: 99%